Badminton overhead backhand and forehand smashes: a biomechanical analysis approach - Rusdiana, A.; Razali Bin Abdullah, M.; Syahid, A. M.; Haryono, T.; Kurniawan, T. (Journal of Physical Education and Sport, 2021)
Smash hit is a powerful weapon to score points in a badminton game. The world record for smash speed is held by Fu Haifeng, a Chinese doubles player who achieved the shuttlecock speed of 332 km/h at the June 2005Sudirman Cup championship. Meanwhile, the fastest backhand smash was conducted by Taufik Hidayat, an Indonesian player who won a gold medal at the 2004 Athens Olympics and achieved the shuttlecock speed of 206 km/h. The purpose of study was to analyze the movement of overhead backhand and forehand smash stroke techniques in a badminton game using a biomechanical approach. The results were analyzed using a descriptive and quantitative approach. Furthermore, 18 male Indonesia badminton national team elite players with an average age of 24.4 ± 1.89 years, height of 1.77 ± 0.19 m, and weight of 66.35 ± 3.7 kg were used. The study was conducted using 3 handycams, a calibration set, a dartfish pro motion analysis software, an automatic shuttlecock launcher shooting machine, and a speed radar gun. The data normalization from the kinematics values of the shoulder, elbow, and wrist joint motion was calculated using the inverse dynamics method. In addition, a one-way ANOVA test was used to identify the differences in the kinematics of motion between two different groups (overhead forehand and backhand smashes). The obtained results showed that the shuttlecock speed during the forehand smash was greater than that during the backhand smash. During the maximal shoulder external rotation phase, two variables were found to have the best results during the forehand smash, i.e., the velocity of shoulder external rotation and wrist palmar flexion. During the maximum angular velocity phase, the velocity of shoulder internal rotation, elbow extension, and forearm supination was higher when making a forehand smash stroke. The main contribution to upper limb motion during overhead backhand and forehand smashes was the internal rotation velocity of the shoulder joint, elbow angular extension, and wrist falmar flexion.